2013
DOI: 10.1007/s12571-013-0241-4
|View full text |Cite
|
Sign up to set email alerts
|

Food security in South Africa—first steps toward a transdisciplinary approach

Abstract: The Stellenbosch University Food Security Initiative provides a platform on which a range of research projects has been developed, spanning different faculties and departments, including the health sciences, agricultural sciences, engineering, and the social sciences. Drawing on a selection of these projects, some of which are published in a special section of this issue of Food Security, the paper highlights key emerging findings and their implications for future work in this field in South Africa. It incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Moreover, the issue of food security is a complex one. This has been echoed by many authors (Battersby & McLachlan, 2013;Drimie & McLachlan, 2013;McLachlan & Hamann, 2011;Scherr, 2000;Swilling & Annecke, 2012;Thompson, 1998;Von Braun, 2009;Zimdahl, 2002). For this reason, "a systemic approach is required to address food insecurity" (Drimie & McLachlan, 2013:217).…”
Section: 23: a Note On Food Systemsmentioning
confidence: 95%
“…Moreover, the issue of food security is a complex one. This has been echoed by many authors (Battersby & McLachlan, 2013;Drimie & McLachlan, 2013;McLachlan & Hamann, 2011;Scherr, 2000;Swilling & Annecke, 2012;Thompson, 1998;Von Braun, 2009;Zimdahl, 2002). For this reason, "a systemic approach is required to address food insecurity" (Drimie & McLachlan, 2013:217).…”
Section: 23: a Note On Food Systemsmentioning
confidence: 95%
“…Assuming that forest foods are mainly traded outside main cities, this would indicate less price volatility for such products. Agricultural food price increases impact most severely on the poorest households and particularly so if they are female-headed (Akter and Basher, 2014;Benfica, 2014;Drimie and McLachlan, 2013); the reason may be that such households do not have the asset base required to smooth income or consumption shortfall. A recent study specifically found that asset-poor households are most likely to use forests as part of their coping strategies .…”
Section: Absolute and Relative Food Pricesmentioning
confidence: 99%
“…Thus, food security may simply be understood in terms of availability, access, and utilisation. 8 According to van Zyl and Kirsten 9 this definition has the following implications:…”
Section: What Is Food Security?mentioning
confidence: 99%